Antioxidant and anti-inflammatory activities of ethyl acetate extracts of chub mackerel (Scomber colias): a thorough seasonal evaluation - Cardoso, Carlos (2022)
The seasonal variation of key bioactivities in ethyl acetate extracts of chub mackerel (Scomber colias), an underutilised fish species, was evaluated through a complete monthly sampling. The phenolic content had a seasonal variation, ranging from 39 5 mg GAE/100 g ww (February) to 340 6 mg GAE/100 g ww (October). Ferric reducing antioxidant power (FRAP) increased from 1.3 0.4 lmol Fe2+ Eq/g ww (Jan uary) to 10.3 0.1 lmol Fe2+ Eq/g ww (September). ABTS had no antioxidant activity between June and December, being the highest value in February, 64.3 6.3 lmol Trolox Eq/100 g ww. For phenolic content and FRAP, there was a strong seasonality, which was similar to that of the lipid content. There fore, correlations were high, being R2 0.95 for lipid vs. phenolic contents. Anti-inflammatory activity did not show large changes throughout most part of the year, remaining high in the 70–80% of COX-2 inhi bition. This finding and the seasonality of the antioxidant properties warrant further research